Socio-Economic Benefits from Indian Winery - Dr. Abhishek Kumar (International Journal of Engineering and Management Research, 2021)
With globalization and increasing economy of India, Indian wine industry is growing at a CAGR of 20-25 percent and estimated to US150 million. Uniformity in wine laws, new regulatory policies, tax incentive and increasing spending power of middle class widely spotting wine is a lifestyle drink and increased acceptability in India. The objective of this research paper is to highlight socio economic benefits from Indian winery for people living in the vicinity of wineries. To measure the socio-economic impact, the survey method was used to collect the data from two villages, Govardhan & Dindori from capital city of Indian wine, Nasik. More than 85% of wine production of India has concentrated in Maharashtra mostly in Nasik & Sangli. The research finding shows that Indian winery has significantly contributed in various fields like employability, education, safety & security, assets etc to poor people of this areas.